Halal brand and purchase intention of halal processed food in Malaysia: The influence of brand theory and religious commitment / Mahdi Borzooei - Borzooei, Mahdi (Institute of Graduate Studies, UiTM, 2016)
Halal is extended beyond religious values into the realm of business and trade and is fast becoming a global brand for both Muslim and non-Muslim consumers. Current international markets need a brand that appeals to global religious consumers and buyers with common values and practices. In response, this research develops a model to investigate implementing brand theory and model, as well as religious commitment on Halal purchase intention. In particular, the mediation effect of consumer-brand relationships is another considerable stream of this study. A quantitative survey methodology using self-administered questionnaires has been adopted to collect data for the proposed constructs in the theoretical model. The target sample of this study includes Muslims and non-Muslims in Malaysia by focusing on three ethnic groups (Malays, Chinese and Indians). Structural equation modeling is used to validate the model. The findings of this thesis largely support the hypothesized relationships proposed in the theoretical model. The results of the study indicate that consumer-brand relationships is a completed mediation variable between brand personality appeal, brand personality, and purchase intention. The results also reveal that although religious commitment has direct influence on consumer-brand relationships, it has no significant effect on purchase intention…